KMBARC registry: protocol for a multicentre observational cohort study on non-cystic fibrosis bronchiectasis in Korea. Issue 1 (19th January 2020) - Lee, Hyun; Choi, Hayoung; Sim, Yun Su; Park, Shinhee; Kim, Woo Jin; Yoo, Kwang Ha; Lee, Seung Jun; Kim, Tae-Hyung; Yang, Bumhee; Jeong, Ina; Um, Soo-Jung; Kim, Deog Kyeom; et al.
Abstract : Introduction: Despite the significant disease burden of bronchiectasis in Korea, no large-scale, representative prospective cohort studies have been conducted to evaluate the clinical characteristics of Korean patients with bronchiectasis, indicating an urgent need for cohort studies on bronchiectasis. Methods and analysis: The Korean Multicenter Bronchiectasis Audit and Research Collaboration (KMBARC) is a prospective, non-interventional observational cohort study on bronchiectasis in Korea. The inclusion criteria of this registry are as follows: (1) adult patients (aged ≥18 years) with or without respiratory symptoms (cough, chronic sputum and/or recurrent respiratory infection) and chest computed tomography revealing bronchiectasis affecting one or more lobes and (2) stable status at the time of registration: patients with bronchiectasis who were admitted for a respiratory aetiology can be enrolled at least 4 weeks after hospital discharge. The exclusion criteria are as follows: (1) bronchiectasis due to cystic fibrosis; (2) traction bronchiectasis associated with interstitial lung disease; (3) patients actively being treated for pneumonia, pulmonary tuberculosis or non-tuberculous mycobacterial infection; (4) patients who are unable or unwilling to provide informed consent; and (5) pregnant patients. Although the KMBARC questionnaires for baseline and annual follow-up data are similar to the European Multicentre Bronchiectasis Audit and Research Collaboration questionnaires, KMBARC has distinctive features such as use of Bronchiectasis Health Questionnaires, measurement with fatigue and depression scales, blood tests, use of consensus definition of exacerbations and information on emergency room or hospitalisation. We aim to recruit at least 1200 patients over the study period from more than 26 hospitals in South Korea. Patients will undergo a detailed baseline and yearly assessment for up to 5 years. The study objectives of the KMBARC registry are as follows: (1) uncovering the natural course of bronchiectasis; (2) aiding in establishing evidence-based bronchiectasis guidelines in Korea; and (3) encouraging and facilitating studies on bronchiectasis in Korea. Ethics and dissemination: This study received necessary approval from the Institutional Review Boards of all participating institutions. The Asan Medical Center Institutional Review Board gave overall approval for the study. Results will be disseminated via peer-reviewed publications and conference presentations. Trial registration number: KCT0003088.